Biomonitoring of several toxic metal(loid)s in different biological matrices from environmentally and occupationally exposed populations from Panasqueira mine area, Portugal - Coelho, P. (2015)
In the Panasqueira mine area of central Portugal, some environmental media show higher metal(loid) concentrations when compared with the local geochemical background and the values proposed in the literature for these environmental media. In order to evaluate the effect of the external contamination on selected indexes of internal dose, As, Cd, Cu, Cr, Fe, Hg, Mg, Mn, Mo, Ni, Pb, S, Se, Si, and Zn were quantified by inductively coupled plasma mass spectrometry and inductively coupled plasma optical emission spectrometry in blood, urine, hair and nail samples from individuals environmentally (N = 41) and occupationally exposed (N = 41). A matched control group (N = 40) was also studied, and data from the three groups were compared. Results obtained agreed with those reported by environmental studies performed in this area, pointing to populations living nearby and working in the mine being exposed to metal(loid)s originated from mining activities. Arsenic was the element with the highest increase in exposed populations. The concentration of other elements such as Cr, Mg, Mn, Mo, Ni, Pb, S, Se, and Zn was also increased, although at a lesser extent, specifically in the individuals environmentally exposed and in females. These findings confirm the need for competent authorities to act as soon as possible in this area and implement strategies aimed to protect exposed populations and the entire ecosystem.